Government’s Role in Preventing the Theft During and After Natural Disasters - Ambara Dewita Purnama; M. Syukri Akub; Hijrah Adhyanti Mirzana (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
Weak supervision and security during and after natural disasters have created new problems. Crime of theft is now rife at the time and after natural disasters. This study aims to determine the government's role in preventing theft during and after natural disasters in the city of Palu. This research is an empirical legal research with a criminological approach. The study was conducted in Palu City, Central Sulawesi. The results of this study indicate that the government's role in efforts to prevent  theft can only overcome theft crimes that are motivated by urgent need of victims of natural disasters and cannot cope with theft that are motivated by opportunity.